A Feminist Stylistic Study : Female Depiction Through the Choice of Transitivity in English Fiction: A Feminist Stylistic Study - AlSakkaf, Ghazal; Öztürk, A. Serdar (Journal of History Culture and Art Research, 2024)
The current study aims to investigate the depiction of women in English fiction through the choice of transitivity. It also intends to prove that female writings can be interpreted in terms of gender bias in literary language. To fulfill those two aims, a contemporary English novel is selected as a sample. It is Brick Lane by the English novelist Monica Ali. The study uses two methods of analysis, quantitative and qualitative. Quantitatively, Wmatrix, a software, is used to sort out the number of transitive and intransitive processes that are mostly used in the text. Then, the occurrences and frequencies of the processes are calculated to find out who scores higher ratios of being initiators or actors and who scores less ratios of being goals or receivers, males, or females. Qualitatively, the findings of the calculations are interpreted in terms of activity and passivity. Results show that female characters score fewer ratios of being initiators or doers for most of the processes than male characters, particularly in performing intentional material processes. Instead, they appear more in the position of receivers and goals for most of processes. So, females are represented as less active than male characters in this novel. The study attributes those results to social and cultural factors.